2020
DOI: 10.1021/acs.est.0c04066
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Pesticide Mixtures in Australian Rivers Discharging to the Great Barrier Reef

Abstract: Rivers discharging to the Great Barrier Reef carry complex pesticide mixtures. Here we present a first comprehensive ecotoxicological risk assessment using species sensitivity distributions (SSDs), explore how risk changes with time and land use, and identify the drivers of mixture risks. The analyzed data set comprises 50 different pesticides and pesticide metabolites that were analyzed in 3741 samples from 18 river and creek catchments between 2011 and 2016. Pesticide mixtures were present in 82% of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Increased turbidity due to elevated total suspended sediments alongside increased phytoplankton biomass as a result of eutrophication cause a decrease in the amount of photosynthetically active radiation available to aquatic photosynthetic organisms such as seagrasses, macroalgae and microalgae [25–27]. Diuron, a PSII-inhibiting herbicide, was chosen based on Queensland catchment and marine monitoring data adjacent to the Great Barrier Reef (GBR) [20,28–31] that indicates it is one of the most frequently detected pesticides year-round in waters entering the GBR [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased turbidity due to elevated total suspended sediments alongside increased phytoplankton biomass as a result of eutrophication cause a decrease in the amount of photosynthetically active radiation available to aquatic photosynthetic organisms such as seagrasses, macroalgae and microalgae [25–27]. Diuron, a PSII-inhibiting herbicide, was chosen based on Queensland catchment and marine monitoring data adjacent to the Great Barrier Reef (GBR) [20,28–31] that indicates it is one of the most frequently detected pesticides year-round in waters entering the GBR [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Increased turbidity due to elevated total suspended sediments alongside increased phytoplankton biomass as a result of eutrophication cause a decrease in the amount of photosynthetically active radiation available to aquatic photosynthetic organisms such as seagrasses, macroalgae and microalgae [25][26][27]. Diuron, a PSII-inhibiting herbicide, was chosen based on Queensland catchment and marine monitoring data adjacent to the Great Barrier Reef (GBR) [20,[28][29][30][31] that indicates it is one of the most frequently detected pesticides year-round in waters entering the GBR [32,33]. The aims of this research were (i) to predict the nonlinear effects of diuron exposure, DIN enrichment and reduced light on two response variables, photosynthesis and growth; (ii) to identify how interaction types for the two response variables vary over different exposure durations; and (iii) to compare the interaction types for the two response variables at the same experimental treatment levels.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides and other pesticides are known to dominate contaminant mixtures found in river systems influenced by agricultural areas (Brodie et al 2015; Devlin et al 2015; Rasmussen et al 2015; Schreiner et al 2016; Bartley et al 2017; Szöcs et al 2017; Lambropoulou et al 2018; Spilsbury 2018; Warne et al 2020). Spilsbury (2018) analyzed 3757 grab samples from the Great Barrier Reef Catchments Loads Monitoring Program (Huggins et al 2018) and found the number of different pesticides detected (i.e., concentrations were greater than the chemical's LOR in each sample varied from 0–23).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] They can also be used to carry pesticides and release them in a controlled way, reducing the total amount of pesticide that needs to be applied and thereby reduce adverse impacts on non-target organisms. 10,11 The wide and large use of pesticides is currently causing a significant risk to the aquatic environments (both autotrophs and heterotrophs species) [12][13][14] and measures for reducing their concentrations in waters are therefore coveted. 15,16 Silica NMs (or nanocomposites containing silica) are particularly suitable for use in applications mentioned above because of their facile preparation and a number of unique properties, including thermal stability, mechanical strength, tunable structure (shape and porosity), biocompatibility and a surface allowing functional modifications.…”
Section: Introductionmentioning
confidence: 99%